“Find Your Happy Place”: A Study on Characterization and the Meaning of Happiness in Trolls (2016) - Nerissa Angela Tayongka (KLAUSA (Kajian Linguistik, Pembelajaran Bahasa, dan Sastra), 2018)
This study aims to identify the characterization of the two main characters in Trolls and how the film portrays the meaning of happiness through its scenes. The process of analyzing characterization is done using direct and indirect characterization along with non-verbal channels of expressions. While to analyze the meaning of happiness, the PERMA model and the theory of acculturation are employed. This is a descriptive qualitative study with the writer herself as the instrument. Based on the analysis, Poppy is optimistic, brave, fair, sincere, warm-hearted, cheerful, trustworthy, and confident. Branch is normative, boring, overly-cautious, and detached. These two characters have different perspective on life, but by the end of the film, they succeed in uniting their mind. Based on the characterization analysis, meaning of happiness can be drawn in two distinct classifications, personal and social happiness. Personal happiness is achieved by fulfilling the five elements of PERMA while social happiness refers to the relationship between trolls and bergens. For them, happiness can be achieved without cutting throat, by being frank, by increasing tolerance, and by helping each other.